2001
DOI: 10.1073/pnas.201394198
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors activate atrial natriuretic peptide in the rat heart

Abstract: In this study, semiquantitative reverse transcription-PCR analysis showed that estrogen receptor ␣ (ER␣) and ␤ (ER␤) mRNAs are developmentally regulated in the rat heart. We found that ER␣ mRNA was low in all heart chambers of 4-day-old rats, but was elevated in the atria (6-to 18-fold) and ventricles (3-to 4-fold) of adult rats. Western blotting analysis confirmed that these differences were efficiently translated into 67-kDa ER␣ protein. ER␤ mRNA was expressed at its highest level in the left atrium and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
3
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 48 publications
8
65
3
1
Order By: Relevance
“…We observed that ERα expression rises from low levels on postnatal D1, whereas ERβ mRNA decreases by postnatal D21 in the rat heart, suggesting a specific role for both receptors in heart maturation. These results are in agreement with previous study in which high ERβ expression was observed in the newborn heart and at 4 days of postnatal life [23], when extensive hyperplasia of the rat heart occurs and the heart grows more rapidly than the body [11]. In adult rats, ERβ expression is low, in contrast to relatively high ERα mRNA levels.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that ERα expression rises from low levels on postnatal D1, whereas ERβ mRNA decreases by postnatal D21 in the rat heart, suggesting a specific role for both receptors in heart maturation. These results are in agreement with previous study in which high ERβ expression was observed in the newborn heart and at 4 days of postnatal life [23], when extensive hyperplasia of the rat heart occurs and the heart grows more rapidly than the body [11]. In adult rats, ERβ expression is low, in contrast to relatively high ERα mRNA levels.…”
Section: Discussionsupporting
confidence: 93%
“…Because a maximal response was observed for treatment with 10 Ϫ7 M AVP, this concentration was used throughout the study. (12).…”
Section: Methodsmentioning
confidence: 99%
“…A similar procedure was applied for amplification of rat ANP mRNA and for 18S mRNA, used as internal standard for semiquantitative gene expression analysis (Jankowski et al 2001). Control RT-PCRs were conducted by omitting reverse transcriptase or RNA from the reaction mixture.…”
Section: Total Rna Extraction and Pcrmentioning
confidence: 99%
“…The actions of estrogen and progesterone are mediated by specific-binding sites present in vascular tissue (Taylor & Al-Azzawi 2000, Critchley et al 2001 and heart (Jankowski et al 2001), through stimulation of endothelial nitric oxide and cGMP (Darkow et al 1997, Rosenfeld et al 2000, and through stimulation of the release and/or synthesis of cardiac natriuretic peptides and oxytocin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation